Генезіс поняття привабливості партнерів - Райко, Діана Валеріївна (Прикарпатський національний університет, 2009)
Проведено аналіз літературних джерел щодо визначення поняття привабливості партнерів; наведено своє визначення, відмінністю якого є те, що привабливість у контексті маркетингу - це властивість підприємства–партнера задовольняти інтереси підприємства-виробника в процесі співпраці щодо випуску продукції або надання послуг.

The analysis of the literature sources was held to state the definition of partnerts attractiveness the self-composed definition is offered which is different by the fact that the partnerts attractiveness in contexts of marketing is considered to be an ability to compete, as the majority of documents declare, but the condition of the household subject which allows to satisfy exact needs of the owners, workers, consumers, partners in comparison with the other subjects at the more attractive conditions.
Genesis of word partnerts attractiveness
Keywords: маркетинг партнерський; співпраця; випуск продукції; інтеграція; структура корпоративна; управління стратегічне; процес виробничий; взаємодія інтерактивна; філософія бізнесу; термін